Respuesta :
x= -4 and x=8
f(x) =6║x-2║+3
39= 6║x-2║+3
36=6║x-2║
6=║x-2║
-(x-2)=6
-x+2=6
x=-4
x-2=6
x=8
f(x) =6║x-2║+3
39= 6║x-2║+3
36=6║x-2║
6=║x-2║
-(x-2)=6
-x+2=6
x=-4
x-2=6
x=8
For the given function [tex]f(x) = 6|x-2| +3[/tex] , [tex]f(x) = 39[/tex] for [tex]x=-4[/tex] and [tex]x=8[/tex].
What is function?
" Function is defined as the relation between the variables such that for each input there exist one and only one output."
According to the question,
Given function,
[tex]f(x) = 6|x-2| +3[/tex]
[tex]|x| = x[/tex]
For , [tex]x= -8[/tex]
[tex]f(-8) = 6|-8-2|+3[/tex]
[tex]= 6\times 10 +3\\\\= 63[/tex]
For, [tex]x= 4[/tex]
[tex]f(4) = 6|4-2|+3[/tex]
[tex]= 6\times 2 +3\\\\= 15[/tex]
For , [tex]x= 8[/tex]
[tex]f(8) = 6|8-2|+3[/tex]
[tex]= 6\times 6 +3\\\\= 39[/tex]
For, [tex]x= -4[/tex]
[tex]f(-4) = 6|-4-2|+3[/tex]
[tex]= 6\times 6 +3\\\\= 39[/tex]
For, [tex]x=9[/tex]
[tex]f(9) = 6|9-2|+3[/tex]
[tex]= 6\times 7 +3\\\\= 45[/tex]
For, [tex]x=-10[/tex]
[tex]f(-10) = 6|-10 -2|+3[/tex]
[tex]= 6\times 12 +3\\\\= 75[/tex]
Hence, for the given function [tex]f(x) = 6|x-2| +3[/tex] , [tex]f(x) = 39[/tex] for [tex]x=-4[/tex] and [tex]x=8[/tex].
Learn more about function here
brainly.com/question/12431044
#SPJ2